(untitled) (MAUSAM, 1964)
In this paper the available data for atmospheric potential gradient near the ground for Colaba (Bombay) and Poona have been studied and discussed with reference to the ground deposition levels of mixed fission products with a view to find out possible variation of the atmospheric potential gradient on account of nuclear explosions. It is seen that there is no secular change in the atmospheric potential gradient due to nuclear explosions. As evidence in respect of Indian stations is in disagreement with that in respect of certain stations in Europe, further investigation of the problem on a world-wide basis is necessary.